Second Five Year Plan of Mysore Statements A to F Part II - Planning Commission (Planning Commission, 1955)
Agriculture and Community Development, National Extension Service Scheme Animal Husbandry and Dairying National Extension Service Programme, Warehousing And Marketing Animal Husbandry and Dairying Warehousing and Marketting Mysore Forest Department.
Government of Mysore